Organisational performance in the post-COVID era led by top leadership: Focus on the mediating effects of value co-creation mindset - Hiroko Oe; Yasuyuki Yamaoka (Health Economics and Management Review)
In the midst of the transformations brought about by COVID-19 in contemporary society, new approaches and leadership styles are essential to ensure organizational success and sustainability. This paper aims to explore the significance of a mindset focused on co-creating value as a support for post-COVID-19 organizational performance and quantitatively validate its impact. Under the influence of COVID-19, it has become evident that conventional approaches alone are insufficient to guarantee the quality of organizational management. In a context where traditional management models no longer suffice, organizations must possess the capacity for adaptation and transformation. To achieve this, the fostering of a shared value co-creation mindset within the organization is crucial. The paper investigates the mediating effect of a value co-creation mindset on the relationship between top leadership and business performance within the framework of total quality management (TQM). By employing quantitative methods and analyzing 300 datasets collected from an online survey, this study examines the direct and indirect effects of top management leadership on performance, highlighting the mediating role played by the value co-creation mindset. The findings reveal a noteworthy insight into the dynamics of leadership and organizational culture in the post-COVID-19 era. While the direct impact of top management leadership on performance appears to be insignificant, the indirect influence mediated by the adoption of a value co-creation mindset is highly relevant. This suggests that the significance of top management leadership lies in its ability to foster an internal culture that facilitates trust-building between top management and employees and encourages value co-creation. In the context of the co-existence with COVID-19 in the foreseeable future, the implications of these findings are profound. It is evident that organizational sustainability and success hinge not solely on leadership with a clear message but also on the cultivation of shared values as an integral part of the organizational culture. As organizations navigate the challenges and opportunities presented by the post-COVID-19 landscape, the role of leadership and the cultivation of a value co-creation mindset emerge as pivotal factors in charting a course towards enduring success and resilience.